2017
DOI: 10.3389/fphar.2017.00282
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Interleukin-1 Pathway in Osteoarthritis: Interleukin-1α and -1β, and NLRP3 Inflammasome Are Not Involved in the Pathological Features of the Murine Menisectomy Model of Osteoarthritis

Abstract: Background: Innate immune response components such as toll-like receptors (TLRs) and NLRP3-inflammasome act in concert to increase IL-1α/β secretion by synovial macrophages. Previous results suggest that IL-1α/β could be an important mediator involved in the pathogenesis of osteoarthritis (OA).Objectives: The aim of our study was to evaluate the role of NLRP3, IL-1β, and IL-1α in the menisectomy (MNX) model of murine OA.Methods: Murine chondrocytes (CHs) and bone marrow-derived machrophages (BMDM) were stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 73 publications
(98 reference statements)
4
56
0
1
Order By: Relevance
“…The IL‐1 pathway may mediate OA pain through pathways in the peripheral and central nervous systems . In some, but not all, animal models of OA, blocking of the IL‐1 pathway improves disease manifestations . However, in clinical trials in knee OA patients not selected for synovitis, an IL‐1R antagonist (anakinra) or an antibody to IL‐1R1 (AMG 108) did not meet the primary symptom‐based study end points.…”
Section: Introductionmentioning
confidence: 99%
“…The IL‐1 pathway may mediate OA pain through pathways in the peripheral and central nervous systems . In some, but not all, animal models of OA, blocking of the IL‐1 pathway improves disease manifestations . However, in clinical trials in knee OA patients not selected for synovitis, an IL‐1R antagonist (anakinra) or an antibody to IL‐1R1 (AMG 108) did not meet the primary symptom‐based study end points.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Nasi et al recently demonstrated that the two forms of IL-1 (IL-1␤ and IL-1␣) were not key mediators in the progression of OA. 60 These results highlight the potential gaps in our understanding of the etiology of OA. Despite these major challenges, several other agents that target inflammatory diseases are clinically available and have demonstrated positive clinical results for the treatment of cardiovascular disease (IL-1␤ monoclonal antibody, Canakinumab), 62 psoriasis (IL-17 antibody, Ixekizumab), 63 and psoriatic arthritis (IL-17, Secukinumab), [64][65][66] but longitudinal observations to elucidate their clinical potential for the treatment of OA-related inflammation are necessary.…”
Section: Interleukin Inhibitorsmentioning
confidence: 91%
“…In fact, Nasi et al . recently demonstrated that the two forms of IL‐1 (IL‐1β and IL‐1α) were not key mediators in the progression of OA . These results highlight the potential gaps in our understanding of the etiology of OA.…”
Section: Growth Factor Therapies and Platelet‐rich Plasmamentioning
confidence: 92%
See 2 more Smart Citations